2000
DOI: 10.1071/wr99072
|View full text |Cite
|
Sign up to set email alerts
|

Morphological change and fat accumulation in juvenile red foxes (Vulpes vulpes) in the Central Tablelands of New South Wales

Abstract: Juvenile red foxes (Vulpes vulpes) reach sexual maturation within 10 months of parturition. During this time juveniles need to manage their energy reserves to fuel maintenance metabolism, growth and reproduction. To determine juvenile growth rates and body energy reserves, I measured body mass, morphology, and estimated body fat, in free-living red foxes from approximately 8 weeks of age through to 1 year old. Foxes (n = 163) were sampled monthly from August 1995 to July 1996 in the Central Tablelands of New S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This was in contrast to our prediction that fresh meat baits would achieve a greater predator knockdown, especially for canines, and is in contrast to several bait palatability trials. For example, Gentle (2005) inserted trackers into fresh meat and dry processed fox baits to assess whether they were eaten or cached following removal. He found that fresh meat baits were eaten at a vastly higher rate relative to dry processed baits.…”
Section: Fresh Baits Are Not More Effective Than Dried Baitsmentioning
confidence: 99%
“…This was in contrast to our prediction that fresh meat baits would achieve a greater predator knockdown, especially for canines, and is in contrast to several bait palatability trials. For example, Gentle (2005) inserted trackers into fresh meat and dry processed fox baits to assess whether they were eaten or cached following removal. He found that fresh meat baits were eaten at a vastly higher rate relative to dry processed baits.…”
Section: Fresh Baits Are Not More Effective Than Dried Baitsmentioning
confidence: 99%
“…Legge et al 2018;Ruykys and Carter 2019) will demand greater resources than do short-term fox control programs (cf. Greentree et al 2000;Gentle 2005). For the former, accuracy is imperative as density approaches zero, and elimination of predators from the control area, whereas for the latter, a trend model may suffice as evidence of the expected decline.…”
Section: Introductionmentioning
confidence: 99%